Assessment of Greenhouse Gas Emissions and Water Quality in Relation to Tourism and Human Activities at Kenyir Lake, Terengganu - Hassan Nurul Husna; Rahman Norshahida; Zawawi Mohd Hafiz; Hayana D. (E3S Web of Conferences)
This study assesses the impact of tourism and human activities on greenhouse gas (GHG) emissions and water quality at Kenyir Lake, Terengganu. Kenyir Lake, a tourist destination in Malaysia, faces environmental challenges due to increased anthropogenic activities. The research quantifies GHG emissions from various sources such as forest land management, land conversion to flooded areas, aquaculture, domestic wastewater, and solid waste disposal using IPCC guidelines. The total GHG emissions from these activities amounted to 151,527 tCO2-eq/year, highlighting the substantial contribution of tourism and human activities to climate change. Water quality was evaluated through the analysis of parameters including Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), ammonia nitrogen (NH3N), total phosphorus (TP), and total nitrogen (TN). Samples were collected from resorts, houseboats, aquaculture farms, and parks during wet and dry seasons. The findings indicate that houseboat areas significantly contribute to high levels of BOD (up to 8.73 mg/l), COD (up to 69.23 mg/l), TSS (up to 303.39 mg/l), and NH3-N (up to 2.64 mg/l), with seasonal variations reflecting the influence of runoff and water volume on pollutant concentrations. These results underscore the need for effective pollution control and sustainable tourism practices to preserve Kenyir Lake’s ecological balance and reduce its GHG footprint.